Medicare's annual wellness visit: 10 years of opportunities gained and lost. Issue 10 (17th August 2022) - Coll, Patrick P.; Batsis, John A.; Friedman, Susan M.; Flaherty, Ellen
Abstract: Medicare annual wellness visits (AWV) were initiated 10 years ago. Though AWVs emphasize on disease prevention and health promotion for older adults was a huge step forward, the current "one size fits all" approach does not adequately meet the wellness needs of a diverse population of older adults. Current AWVs do not sufficiently take into consideration the medical, psychological, functional, racial, cultural and socio‐economic diversity of older adults. Updated AWVs should be tailored to meet the needs and priorities of older adults receiving them. Several geriatrics approaches to care, including geriatrics Glidepaths and the 4Ms of an Age‐Friendly Health System, could help develop and guide a more patient‐specific geriatrics focused approach to AWVs. Medicare's IPPE is an ideal time to advise new Medicare beneficiaries regarding what they should and should not do to maximize their ability to be healthy and functionally independent into their 80s, 90s, and 100s.